2014
DOI: 10.1080/09205063.2014.898124
|View full text |Cite
|
Sign up to set email alerts
|

Nerve cells culture from lumbar spinal cord on surfaces modified by plasma pyrrole polymerization

Abstract: Currently, there are several techniques for modified cell culture surfaces under research to improve cell growth and adhesion. Recently, different methods have been used for surface coating, using biomolecules that enhance cell attachment and growth of nerve cells from spinal cord, such as the use of Poly-DL-Ornithine/Laminin. Plasma-polymerized pyrrole (PPy)-treated surfaces have showed improvement on surfaces biocompatibility with the cells in culture since they do not interfere with any of the biological ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
0
14
0
17
Order By: Relevance
“…The plasma reactor is described in a previous work 17 , is formed of a pyrex glass tube of 25 cm length, 9 cm of external diameter and 5 mm thickness, each end of the tube is sealed by a stainless steel lids and in each lid there are two access ports and one central access, where one electrode for plasma discharge is introduced. In a lid and using the access ports, a pirani probe (Edwards) is placed to measure the pressure inside the discharge chamber, by the other access a vacuum system is connected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma reactor is described in a previous work 17 , is formed of a pyrex glass tube of 25 cm length, 9 cm of external diameter and 5 mm thickness, each end of the tube is sealed by a stainless steel lids and in each lid there are two access ports and one central access, where one electrode for plasma discharge is introduced. In a lid and using the access ports, a pirani probe (Edwards) is placed to measure the pressure inside the discharge chamber, by the other access a vacuum system is connected.…”
Section: Methodsmentioning
confidence: 99%
“…Among other methods, the polypyrrole synthesized by plasma (PPPy) and iodine-doped (PPPy-I) exhibit an extraordinary capacity as culture cell support. Different cell types have been seeded and proliferated on biocompatible scaffolds coated by PPPy 16,17 . One of the most important applications is based on the implementation of mesoparticles of PPPy doped with iodine for spinal cord injury treatment.…”
Section: Introductionmentioning
confidence: 99%
“…One technique that has been shown to be effective in modifying the surface of different polymers is plasma polymerization. Surface modification can be accomplished by depositing a polymeric thin film that has functional groups that allow biomolecules to anchor to the surface (Ramírez-Fernández et al, 2012;Zuñiga Aguilar et al, 2014). Plasma polymerization using pyrrole as monomer has shown reliable performance in producing surfaces that promote cell adhesion and proliferation, especially in in vivo experiments (Ramírez-Fernández et al, 2015;Ruiz Velasco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…14 This improvement has been associated with the chemical species that contains N-H bond, which has been proven to stimulate cell growth. 1517 In this regard, Mejía et al. 18 and Olayo et al., 13 reported that PPy-Mesoparticles, when administered directly into the nerve tissues of rats with spinal cord injury, were successfully integrated into these nerve cells without inducing an acute inflammatory response.…”
Section: Introductionmentioning
confidence: 99%